Cell-mediated drug delivery by gingival interdental papilla mesenchymal stromal cells (GinPa-MSCs) loaded with paclitaxel. (2nd June 2016) - Brini, Anna Teresa; Coccè, Valentina; Ferreira, Lorena M. Josè; Giannasi, Chiara; Cossellu, Gianguido; Giannì, Aldo Bruno; Angiero, Francesca; Bonomi, Arianna; Pascucci, Luisa; Falchetti, Maria Laura; Ciusani, Emilio; Bondiolotti, Gianpietro; et al.
ABSTRACT: Objective : Gingival tissue is composed of cell types that contribute to the body's defense against many agents in oral environment, wound healing and tissue regeneration. Thanks to their easy and scarcely invasive withdrawal procedure, interdental papilla provide a good source of mesenchymal stromal cells (GinPa-MSCs). We isolated GinPa-MSCs and verified their ability to uptake/release the anticancer agent Paclitaxel (PTX). Methods : In vitro expanded GinPa-MSCs were characterized for CD markers by FACS, tested for differentiation ability and analyzed by TEM. Their ability to uptake/release PTX was assessed according to a standardized procedure. Results : The CD expression and chondro-adipo-osteo differentiation ability confirmed the mesenchymal feature of GinPa-MSCs. Surprisingly, 28% of GinPa-MSCs expressed CD14 marker and had an impressive pinocytotic activity. GinPa-MSCs were able to take up and release a sufficient amount of PTX to demonstrate effective in vitro activity against pancreatic carcinoma cells, suggesting that the drug was not inactivated. Conclusions : The procedure to obtain MSCs from interdental papilla is less invasive than that used for both bone marrow and adipose tissue, GinPa-MSCs are easy to expand and can be efficiently loaded with PTX. Taken together these qualities suggest that GinPa-MSCs may prove to be a good tool for cell-mediated drug delivery in cancer, particularly if related to stomatognathic system.